MoS2-coated ZnO nanocomposite as an active heterostructure photocatalyst for hydrogen evolution. (August 2017) - Zhang, Shibao; Tang, Fumin; Liu, Jinkun; Che, Wei; Su, Hui; Liu, Wei; Huang, Yuanyuan; Jiang, Yong; Yao, Tao; Liu, Qinghua; Wei, Shiqiang
Abstract: To obtain an efficient photocatalyst for solar energy conversion is a key issue in photocatalytic water splitting. Here, we have synthesized MoS2 -coated ZnO nanocomposite photocatalyst and investigated the structure-performance relationship by UV–vis absorption and photoluminescence (PL) spectroscopy. Under the simulated sunlight irradiation, the MoS2 -coated ZnO nanocomposite in aqueous Na2 SO3 solution achieves a high H2 production rate of 1410 μmol/g/h, 5.8 times higher than that of pristine ZnO nanoparticles. The UV–vis spectra and PL results reveal that the MoS2 coated on the surface of ZnO nanoparticles can significantly facilitate the photoexcited electrons transfer and suppress the recombination of the electrons and holes, thus increasing the H2 evolution activity of the composite system. Highlights: Synthesis of the MoS2 -coated ZnO nanocomposite. The photocatalytic H2 evolution rate of the nanocomposite is enhanced. PL results indicate an evident reduction of the photocarriers recombination.